Priority-based model for network partition problems for mobile ad hoc networks. (1st January 2013) - Varaprasad, G.; Wahidabanu, R.S.D.
In mobile ad hoc networks, it is collection of nodes used for communication among the nodes. Due to the node mobility, the network may be divided into a number of parts. This paper proposes a priority-based model for mobile ad hoc networks, which assigns the weights to all nodes. Here, the high-priority nodes must maintain connections against those of low-priority nodes. The proposed model has been simulated with the help of 100 mobile nodes in the network using Network Simulator (NS-2.34). The proposed model was simulated and tested under the various environments. It was compared with Goyal model and Hähner model. The simulation results have shown that the proposed model has reached the top position in terms of the network size, percentage of path reconstruction and average delay.